Peningkatan Literasi Kemiskinan Energi dan Efisiensi Pengeluaran Rumah Tangga Miskin: Pengabdian di Desa Alue Waki Kecamatan Darul Makmur Kabupaten Nagan Raya - Sailal Arimi; Harmaini Harmaini; Yasrizal Yasrizal; Mahrizal Mahrizal; Said Mahdani; Sudarman Sudarman; Zuhrizal Fadhly (Indo Publishing, 2025)
The phenomenon of rural poverty in Indonesia has a strong correlation with limited human capital capacity. The energy literacy deficit that arises from low educational background exacerbates economic vulnerability through inflated household energy consumption costs. This community service aims to increase the capacity of poor households in Alue Waki Village, Darul Makmur District, by strengthening energy poverty literacy based on P3KE (Purpose of Accelerating the Elimination of Extreme Poverty) microdata. The implementation method uses a participatory educational approach that includes counseling on energy-saving habits and technical demonstrations of energy expenditure efficiency to 35 poor household heads. Evaluation of the impact of this service is measured using pre-test and post-test instruments to see changes in knowledge and behavioral intentions. The results of the activity show an accumulative increase in community capacity of 73.1%, with a surge in self-confidence in adopting modern energy technology reaching 97.1%. Economically, this increase in literacy results in potential energy cost savings (projected) of 13.2%, or a decrease from an average of Rp193,500 to an estimated Rp168,000 per month if efficient behavior patterns are consistently implemented. This figure reflects the fiscal space available for poor households to allocate for children's nutrition and education needs. This community service concludes that human capital intervention through energy literacy education is a rational strategy for fostering economic independence for target households.